The Role of Institutions in Alleviating The Vulnerability of Farmers to Poverty in Malaysia: A Longitudinal Study - Senadjki Abdelhak,; Jamalludin Sulaiman,; Saidatulakmal Mohd,; Azlinda Azman, (Kajian Malaysia, 2015)
Institutional support such as social and financial assistance play vital role in helping the poor deal with poverty. Nevertheless, institutions are often criticised for its delayed delivery and weak monitoring of programs. This study attempts to investigate the role of institutions in helping farmers deal with their vulnerabilities to poverty. A structured socio-economic questionnaire from a three-round panel survey undertaken at 6-month interval targeting the farmers in Kelantan and Terengganu, Malaysia is employed. The institution support is investigated in various areas that include effects on amount of production sold, head-count of cows, head-count of sheep and goats, head-count of hens and ducks, food storage and valuable things, savings and finally on farmers vulnerabilities. Results of the study indicate that institutions are inactive in providing assistance and support to farmers. Often, assistance is provided after an occurrence of a shock. Incidentally, the assistance provided does not reach all farmers, partly due to asymmetric information on the availability of the assistance or that farmers are not selected for the assistance. In most occasions, assistance is just not available to the farmers.